The Beneficence of Cuddle Therapy in Hyperekplexia: A Case Report. (February 2020) - Seale, Jamie; Murphy, Jennifer; Mantle, Ashley; Chan, Belinda
Abstract : Background: Benevolent injustice occurs when well-intentioned treatment efforts produce an outcome that limits the potential of a patient. The unintended harm can result in significant moral distress for the family and the healthcare team. Clinical Findings: We discussed an ethical dilemma regarding a neonate who had suspected seizure and hypoxic–ischemic encephalopathy after home birth delivery. The healthcare team experienced moral distress about the mother's desire to not use anti-seizure medications and instead trial other interventions such as cuddling. Subsequently, clinical analysis ruled out a seizure disorder. Genetic studies on this neonate confirmed hereditary hyperekplexia, which presented as exaggerated Moro reflex and apnea that mimicked seizure. Intervention: We discussed how applying any one of the 4 basic ethical principles of autonomy, beneficence, nonmaleficence, or justice could counteract benevolent injustice and moral distress. Outcomes: Discussions with the patient's mother and nurse allowed the team to overcome their reluctance to try the mother's treatment recommendations. This resulted in adopting the seemingly counterintuitive intervention of cuddling that turned out to be effective for this neonate with hereditary hyperekplexia. Practice Recommendations: The moral distress associated with benevolent injustice should be identified early to minimize long-term consequences to the patient, family, and healthcare team. Healthcare teams should learn to apply ethical principles when discussing patient care concerns in an unbiased manner. Guided ethical discussions allow us to be more efficient in providing family-centered care that aligns with the patient's best interest.